(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Although analytical thinking, creative thinking and critical thinking are among the thoughts that express the personal nature of a person, but the main purpose of this research is to connect the students’ analytical thinking ability with critical thinking and creative thinking at the same time and the nature of all three thoughts. In the development and formation of education and training of students from family to kindergarten, from kindergarten to school and higher levels of education, it will be analysed and investigated. It is more important to relate analytical thinking to creative thinking and critical thinking in predicting changes in students’ academic progress at the same time as all three thoughts are together because it is one of the factors that form the individuality of human nature and plays a fundamental role in the formation of a student’s worldview. In the elementary courses, one plays. The ability to think critically and analytically is one of the main competencies expected of a learning process in higher education institution, especially in science area. A scientist should be able to explore a problem, choose the appropriate method, obtain the solutions, and communicate their analysis correctly.